Cattaneo-Christov (CC) heat flux model for nanomaterial stagnation point flow of Oldroyd-B fluid. (April 2020) - Hayat, T.; Khan, Sohail A.; Ijaz Khan, M.; Momani, Shaher; Alsaedi, Ahmed
Highlights: MHD stagnation point flow of Oldroyd-B fluid is considered. Both heat and mass fluxes are discussed via Cattaneo-Christov model. Thermophoretic and Brownian motion are accounted. Total average residual error is calculated. Abstract: Background Magnetohydrodynamic (MHD) stagnation point flow of Oldroyd-B nanoliquid is discussed in presence of Cattaneo-Christov mass and heat fluxes. Impacts of Brownian motion and thermophoresis are discussed. Convergent solution for nonlinear analysis are organized for velocity, temperature and concentration. Method Average residual error is calculated with the help of optimal homotopy analysis method (OHAM). Results Prominent features of interesting parameters on concentration, velocity and temperature are scrutinized. Velocity field has reverse trend for Deborah number against retardation and relaxation times. Temperature and concentration have similar results versus thermophoresis parameter. Conclusions: 1: Velocity has opposite impact for Deborah number for relaxation and retardation time. 2: Velocity boosts up for higher ratio parameter. 3: Velocity against magnetic parameter is decreased. 4: Thermal upsurges versus thermal relaxation time parameter. 5: Outcomes of thermophoretic parameter and Brownian motion parameter on temperature are quantitatively similar. 6: Concentration boosts up via Brownian parameter. 7: Concentration have similar characteristics for both Prandtl number and thermophoretic parameter.